Modeling the weaning diet of piglets with fermented feed material: effects on growth performance and health parameters - Badaras, Sarunas; Starkute, Vytaute; Mockus, Ernestas; Ruzauskas, Modestas; Klupsaite, Dovile; Mozuriene, Erika; Dailidaviciene, Jurgita; Dauksiene, Agila; Vadopalas, Laurynas; Metzler-Zebeli, Barbara U.; Bartkiene, Elena (Frontiers in Veterinary Science, 2025)
Recently, fermented feed materials (FFM) have gained attention for their potential to improve overall performance in piglets. In this study, the effect of supplementing FFM to the diet of Topigs Norsvin Yorkshire piglets (weaning) on growth performance and health parameters was investigated. The whole experiment was divided into two phases: suckling (days 7 to 25) and weaning (days 25 to 69). During the suckling phase, 36 piglets (divided into three groups of 12 piglets/group) were assigned to three groups to differently ‘program’ their gut: (1) control (C) group, receiving a full-fledged commercial pre-starter feed, and (2) the Pp and (3) Pa groups, which received 25 mL of fermented milk permeate prepared either with Pediococcus pentosaceus LUHS183 and Pediococcus acidilactici LUHS29, respectively. In weaning, the pigs received two diets: C group received a non-fermented basal diet; Pp and Pa—same Lactiplantibacillus plantarum LUHS122, Lactobacillus casei LUHS210, Latilactobacillus curvatus LUHS51, and Lacticaseibacillus paracasei LUHS244 FFM. Results showed that weaned pigs of the Pp and Pa groups had higher body weight on day 69 compared to C group. Feed conversion ratio was similar in all three groups. On day 69, the highest concentration of immunoglobulins IgG was found in Pa group compared to other groups, while plasma alanine aminotransferase (ALT) levels were lower in treated groups compared to the C group. Diet did not influence ALT, aspartate aminotransferase (AST), faecal pH or dry matter content. On day 69, the faeces of the Pp and Pa groups exhibited higher texture hardness compared to the control (C) group. Additionally, the lactic acid bacteria (LAB) count differed significantly between the Pa and control groups. The C group had high abundances of beneficial lactobacilli and Prevotellaceae but the lowest bacterial diversity compared to the Pp and Pa groups. On day 69, faeces of treated groups had greater variability in individual volatile compounds (VCs) compared to the C group. Significant correlations between VC and faecal microbiological parameters were observed. In conclusion, the findings from this study show that with pediococci (LUHS183 and LUHS29), and lactobacilli FFM supports gut microbial diversification and homeostasis, potentially leading to improved BW gain.